2023
DOI: 10.3390/molecules28031496
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Chemistry within the Structured Environment Provided by the Macrocyclic Cores of Carbaporphyrins and Related Systems

Abstract: The unique environment within the core of carbaporphyrinoid systems provides a platform to explore unusual organometallic chemistry. The ability of these structures to form stable organometallic derivatives was first demonstrated for N-confused porphyrins but many other carbaporphyrin-type systems were subsequently shown to exhibit similar or complementary properties. Metalation commonly occurs with catalytically active transition metal cations and the resulting derivatives exhibit widely different physical, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 357 publications
0
8
0
Order By: Relevance
“…22 Altering the macrocyclic core to CNNN decreases reactivity toward metal cations, but carbaporphyrinoid systems still form stable organometallic derivatives. 2,3 Benzocarbaporphyrins behave as trianionic ligands and it has previously been reported that benzo-5 and naphthocarbaporphyrins 17 generate silver(III) complexes when reacted with silver(I) acetate at room temperature. In order to investigate the coordination chemistry of the anthrocarbaporphyrin system, 8 was reacted with silver(I) acetate in an attempt to prepare 17 (Scheme 4).…”
Section: Scheme 3 Synthesis and Protonation Of An Anthrocarbaporphyrinmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Altering the macrocyclic core to CNNN decreases reactivity toward metal cations, but carbaporphyrinoid systems still form stable organometallic derivatives. 2,3 Benzocarbaporphyrins behave as trianionic ligands and it has previously been reported that benzo-5 and naphthocarbaporphyrins 17 generate silver(III) complexes when reacted with silver(I) acetate at room temperature. In order to investigate the coordination chemistry of the anthrocarbaporphyrin system, 8 was reacted with silver(I) acetate in an attempt to prepare 17 (Scheme 4).…”
Section: Scheme 3 Synthesis and Protonation Of An Anthrocarbaporphyrinmentioning
confidence: 99%
“…Carbaporphyrins have unique reactivity and readily form organometallic derivatives with late transition metal cations. 2,3 Much of the work in this area has been conducted on benzo-fused carbaporphyrins 1 (Scheme 1) due in part to ease of synthesis. 4 In principle, ring fusion extends conjugation within these porphyrinoid systems, but in practice, 1 still favors an 18π electron delocalization pathway.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbaporphyrinoid systems, porphyrin-like molecules with one or more carbon atoms within the macrocyclic core, exhibit diverse and unusual reactivity and may exist as aromatic, nonaromatic or antiaromatic species [ 1 , 17 , 18 ]. In addition, carbaporphyrin-type systems react with many late transition metal cations to generate stable organometallic derivatives under mild conditions [ 19 , 20 , 21 , 22 ]. N -Confused porphyrins have been particularly well studied with regard to their metalation properties [ 22 ], but complementary organometallic chemistry has also been described for related systems [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, carbaporphyrin-type systems react with many late transition metal cations to generate stable organometallic derivatives under mild conditions [ 19 , 20 , 21 , 22 ]. N -Confused porphyrins have been particularly well studied with regard to their metalation properties [ 22 ], but complementary organometallic chemistry has also been described for related systems [ 19 , 20 ]. N -Confused porphyrins have two major tautomeric forms, 1a and 1b , that have dramatically different spectroscopic properties.…”
Section: Introductionmentioning
confidence: 99%